Consumer Evaluations of Corporate Brand Deployments - JAJU, Anupam (Institutional Knowledge at Singapore Management University, 2006)
There has been little attention paid to the management of corporate brand names as part of the merger and acquisition process. As an initial step towards developing a better understanding of this brand redeployment decision the authors consider the reactions of one important stakeholder group-consumers-to alternative strategies. Specifically, the authors discuss the importance of the corporate branding decision in the M&A process and present a typology of alternative redeployment strategies as well as an exploratory study examining reactions to different postmerger branding strategies. The authors find evidence that the brand equity related to corporate brands is often decreased as a result of M&A activities and that individuals react differently to mergers employing different redeployment strategies. These results emphasize the need for firms to evaluate the corporate branding component of M&A activities as part of the process of managing corporate brands and should generate interest and research in this managerially relevant area.